An encouraging recyclable synergistic hydrogen bond crosslinked high-performance polymer with visual detection of tensile strength. (October 2018) - Chang, Guanjun; Wang, Cheng; Song, Lixian; Yang, Li
Abstract: We have successfully constructed a novel type of recyclable crosslinked protonated-polybenzotriazole ether sulfone (PBTSH + ), which possessed outstanding thermal stability and mechanical properties. More importantly, the tensile strength of the resulting crosslinked films could be visually detected by taking advantage of the transparency decreasing effect of synergistic hydrogen bonds between protonated benzotriazole units. Graphical abstract: Highlights: Polybenzotriazole ether sulfone was obtained by catalyst-free nucleophilic substitution polycondensation reaction. Crosslinked PBTSH + films were constructed by using synergistic hydrogen bond interactions. Crosslinked PBTSH + films showed good thermal stabilities and encouraging tensile strengths. Crosslinked PBTSH + films can be recycled by a gentle aqueous treatment. Tensile strength of the PBTSH + films could be visual detected by taking advantage of the transparency decreasing effect.